Application of Story-Wise Shear Building Identification Method to Actual Ambient Vibration - Fujita, Kohei; Ikeda, Ayumi; Takewaki, Izuru (Frontiers in Built Environment, 2015)
A sophisticated and smart story stiffness System Identification (SI) method for a shear building model is applied to a full-scale building frame subjected to micro-tremors. The advantageous and novel feature is that not only the modal parameters, such as natural frequencies and damping ratios, but also the physical model parameters, such as story stiffnesses and damping coefficients, can be identified using micro-tremors. While the building responses to earthquake ground motions are necessary in the previous SI method, it is shown in this paper that the micro-tremor measurements in a full-scale 5 story building frame can be used for identification within the same framework. The SI using micro-tremor measurements leads to the enhanced usability of the previously proposed story-wise shear building identification method. The degree of ARX models and cut-off frequencies of band-pass filter are determined to derive reliable results.